An allosteric modulator binds to a conformational hub in the beta(2) adrenergic receptor - Liu, Xiangyu; Kaindl, Jonas; Korczynska, Magdalena; Stößel, Anne; Dengler, Daniela; Stanek, Markus; Hübner, Harald; Clark, Mary J.; Mahoney, Jake; Matt, Rachel Ann; Xu, Xinyu; Hirata, Kunio; et al. (Nature Chemical Biology, 2020)
Most drugs acting on G-protein-coupled receptors target the orthosteric binding pocket where the native hormone or neurotransmitter binds. There is much interest in finding allosteric ligands for these targets because they modulate physiologic signaling and promise to be more selective than orthosteric ligands. Here we describe a newly developed allosteric modulator of the beta(2)-adrenergic receptor (beta(2)AR), AS408, that binds to the membrane-facing surface of transmembrane segments 3 and 5, as revealed by X-ray crystallography. AS408 disrupts a water-mediated polar network involving E122(3.41) and the backbone carbonyls of V206(5.45) and S207(5.46). The AS408 binding site is adjacent to a previously identified molecular switch for beta(2)AR activation formed by I-3.40, P-5.50 and F-6.44. The structure reveals how AS408 stabilizes the inactive conformation of this switch, thereby acting as a negative allosteric modulator for agonists and positive allosteric modulator for inverse agonists.
CRIS-Team WoS Importer:2020-06-16

Hybridization of β-Adrenergic Agonists and Antagonists Confers G Protein Bias - Stanek, Markus; Picard, Louis Philippe; Schmidt, Maximilian; Kaindl, Jonas; Hübner, Harald; Bouvier, Michel; Weikert, Dorothée; Gmeiner, Peter (Journal of Medicinal Chemistry, 2019)
Starting from the β-adrenoceptor agonist isoprenaline and beta-blocker carvedilol, we designed and synthesized three different chemotypes of agonist/antagonist hybrids. Investigations of ligand-mediated receptor activation using bioluminescence resonance energy transfer biosensors revealed a predominant effect of the aromatic head group on the intrinsic activity of our ligands, as ligands with a carvedilol head group were devoid of agonistic activity. Ligands composed of a catechol head group and an antagonist-like oxypropylene spacer possess significant intrinsic activity for the activation of Gα s , while they only show weak or even no β-arrestin-2 recruitment at both β 1 - and β 2 -AR. Molecular dynamics simulations suggest that the difference in G protein efficacy and β-arrestin recruitment of the hybrid (S)-22, the full agonist epinephrine, and the β 2 -selective, G protein-biased partial agonist salmeterol depends on specific hydrogen bonding between Ser 5.46 and Asn 6.55 , and the aromatic head group of the ligands.
CRIS-Team Scopus Importer:2019-06-04

Structure-guided development of dual ß2 adrenergic/dopamine D-2 receptor agonists - Weichert, Dietmar; Stanek, Markus; Hübner, Harald; Gmeiner, Peter (Bioorganic & Medicinal Chemistry, 2016)
Aiming to discover dual-acting beta(2) adrenergic/dopamine D-2 receptor ligands, a structure-guided approach for the evolution of GPCR agonists that address multiple targets was elaborated. Starting from GPCR crystal structures, we describe the design, synthesis and biological investigation of a defined set of compounds leading to the identification of the benzoxazinone (R)-3, which shows agonist properties at the adrenergic beta(2) receptor and substantial G protein-promoted activation at the D-2 receptor. This directed approach yielded molecular probes with tuned dual activity. The congener desOH-3 devoid of the benzylic hydroxyl function was shown to be a beta(2) adrenergic antagonist/D-2 receptor agonist with K-i values in the low nanomolar range. The compounds may serve as a promising starting point for the investigation and treatment of neurological disorders. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: G protein-coupled receptors; Dopamine receptor; beta(2) adrenergic receptor; Neurodegenerative disorders; Parkinson's disease; Molecular probes; Polypharmacology